EFEKTIVITAS PENERAPAN METODE DRILL MELALUI BERNYANYI TERHADAP KEMAMPUAN MENGHAFAL PERKALIAN SISWA KELAS III SDN 09 KOTO BARU - Suci Rahma Putri; Ahmad Ilham Armaryadi; Padlan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research is based on problems in mathematics learning, where the results of mathematics learning in multiplication materials are low and students still do not memorize multiplications from one to ten. Through this problem, the aim of this research is to find out whether the drill method is effective on the motivation and learning outcomes of memorizing multiplication in class III students at SDN 09 Koto Baru. Therefore, researchers will apply the drill method in learning. The type of research used was experimental, Pre Experimental Design. This research was carried out at SDN 09 Koto Baru class III in the even semester of the 2023/2024 academic year. The population in this study was all class III students consisting of one class with a total of 17 students. The development of the instruments used are validity tests, reliability tests and difficulty levels. The data collection technique used was an initial test (pre-test) and a final test (post-test). The data analysis technique for this research uses normality testing and hypothesis testing. Based on the results of the paired samples t test, the significance was 0.000<0.05, meaning that H0 was rejected and Ha was accepted. So it can be concluded that there is effectiveness in applying the drill method through singing on the ability to memorize multiplication for class III students at SDN 09 Koto Baru.